Optimization of microbial biomass protein from low-fat coconut residue using (Rhizopus oligosporus) - Malata, Stella Marie
This study aims to optimize the conditions necessary for microbial biomass protein production from low-fat coconut residue using Rhizopus oligoporus. The first phase represented the proximate analysis of the low-fat coconut residue which contained an average of 27.20% fat, 58.92% fiber, 10.92% protein and 2.16% ash. The results were obtained from three trials and computed on dry basis. The second phase dealt with the optimization of substrate-to-water ratio and the concentration of microbial inoculation. In the production of the microbial biomass protein, the varied substrate-to-water ratios -- 1:0.5, 1:10, 1:15 and three concentration of inoculum namely 10^4 cells/ml, 10^5 cells/ml, 10^6 cells/ml showed a significant difference on the protein content of the enriched low-fat coconut residue flour. At a ratio of 1:10 and spore load of 10^5 cells/ml of Rhizopus oligosporus, the protein content of the enriched low-fat coconut residue flour was increased from 10.92% in the raw material to 28.763%, thus, improving the nutritional quality of the material.